1998
DOI: 10.1104/pp.117.1.255
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Specificity of Barley Cysteine Endoproteases EP-A and EP-B1

Abstract: The cysteine endoproteases (EP)-A and EP-B were purified from green barley (Hordeum vulgare L.) malt, and their identity was confirmed by N-terminal amino acid sequencing. EP-B cleavage sites in recombinant type-C hordein were determined by N-terminal amino acid sequencing of the cleavage products, and were used to design internally quenched, fluorogenic peptide substrates. Tetrapeptide substrates of the general formula 2-aminobenzoyl-P 2 -P 1 -P 1 -P 2 -tyrosine(NO 2 )-aspartic acid, in which cleavage occurs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…Based on our knowledge of EP-B specificity and its hordein cleavage pattern, particularly within the repetitive domains, it is known that many of the peptides released by its action have a Pro residue in the second and/or penultimate position (Davy et al, 1998). This is clearly illustrated by the cleavage products of C hordein, where KPFPVQ, QPFPQ, and QPQ are formed.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Based on our knowledge of EP-B specificity and its hordein cleavage pattern, particularly within the repetitive domains, it is known that many of the peptides released by its action have a Pro residue in the second and/or penultimate position (Davy et al, 1998). This is clearly illustrated by the cleavage products of C hordein, where KPFPVQ, QPFPQ, and QPQ are formed.…”
Section: Discussionmentioning
confidence: 98%
“…Proteins were visualized by silver staining (Bloom et al, 1987). For N-terminal sequencing, proteins were blotted onto polyvinylidene fluoride (PVDF) membrane (Immobilon P, Millipore, Bedford, MA) using a semidry electroblotter (Aricos, Ølstykke, Denmark), as previously described (Davy et al, 1998).…”
Section: Protein Determination Sds-page and Blottingmentioning
confidence: 99%
See 2 more Smart Citations
“…Zhang and Jones (1995) reported that 27 Cys-proteases are among the 42 proteases that are involved in the germination of barley (Hordeum vulgare) seed. Until now, few of these proteases have been characterized (Koehler and Ho, 1990;Davy et al, 1998), and there are currently only limited data on the effects of the inhibitors required for their regulation (Martinez et al, 2005b). In contrast, sets of genes encoding transcriptional factors synthesized in response to phytohormones have been implicated in controlling hydrolase activity during barley seed germination (Gubler et al, 1999;Sreenivasulu et al, 2008).…”
Section: ([Lvi]-[agt]-[rke]-[fy]-[as]-[vi]-x-[edqv]-mentioning
confidence: 99%